Developing Pop-Up Book for Teaching Vocabulary to Young Learners - Siti Khadijah; Yanti Sri Rezeki (FKIP - Universitas Tanjungpura, 2023)
This research aimed to develop a pop-up book for teaching vocabulary to young learners, specifically kindergarten students at Darul Ulum Kindergarten. The study followed the ADDIE model, consisting of the phases of analysis, design, and development. In the analysis phase, the researcher determined the appropriate materials and criteria for the media to be used by teachers and students in learning vocabulary. The design phase focused on the criteria of the media for children and the materials used in the book. The development phase involved creating the essential parts of the media. Based on the assessment rubric used by the teacher, the pop-up vocabulary book received a score of 96.875%, indicating that it is feasible for use in teaching vocabulary to young learners.